THE PROPAGATION OF THE LECANICILLIUM LECANI WITH LIQUID MEDIA - Amirul Mu'minin; Fita Fitriatul Wahidah (Jurnal Matematika dan Sains (JMS), 2021)
The Lecanicillium lecanii is an entomopathogenic biological agent that can be used to control plant pest organisms. This study aimed to determine the use of liquid media derived from boiled potato water as a propagation material for the Lecanicillium lecani. The propagation of the fungus starts from propagation on PDA (Potato Dextrose Agar) sloping agar media, propagation or inoculation of the fungus on solid media (rice), then propagation of the fungus on liquid media (potato boiled water). The results of this activity showed that liquid media (potato boiled water) can be used as a medium for propagation of the Lecanicillium lecanii because potatoes have a starch content with good nutrients and carbohydrates to be used as growth media for entomopathogenic for example is Lecanicillium lecanii.